Crosslinked network formation beyond graft copolymers in transparent bisphenol-A Polycarbonate/Poly(methyl methacrylate) blends catalyzed by bis(trifluoromethanesulphonyl)imide based organic salts. (3rd May 2021) - Yan, Tingzi; Xu, Huihui; Li, Yongjin
Abstract: It has been widely accepted that the promoted transparency of bisphenol-A Polycarbonate/Poly(methyl methacrylate) (PC/PMMA) blends was attributed to the transesterification induced PC-graft(g)-PMMA copolymer formation during melt extrusion of the blends. However, prior studies fall short of detailed characterization of the PC-g-PMMA copolymers. In this paper, we investigated the effect of different bis(trifluoromethanesulphonyl)imide-based salts on the compatibilization and optical transparency properties of PC/PMMA blends. It was found that Mg(TFSI)2 showed the best compatibilization effect and could enable transparent blend films for PC/PMMA blends at all PMMA compositions as manifested from scanning electron microscopy (SEM) images, differential scanning calorimetry(DSC) and thermogravimetric analysis(TGA). Moreover, elution experiments with mutual solvent left intractable portion indication crosslinked network formation beyond PC-g-PMMA copolymers. Finally, the detailed structure of PC-g-PMMA copolymers was studied by Gel Permeation Chromatography (GPC). To the best of our knowledge, this is the first time to analyze the detailed structure of the PC-g-PMMA copolymers formed during melt extrusion. Graphical abstract: Image 1 Highlights: Mg(TFSI)2 showed the best compatibilization effect for PC/PMMA blends among four TFSI based organic salts. Crosslinked network formation was detected in the melt extrusion PC/PMMA blends with Mg(TFSI)2 . Detailed structures of PC-g-PMMA copolymers were characterized by GPC.